Kebijakan Tugas Pokok Guru sebagai Wujud Pembentukan Jiwa Kepemimpinan di SPS Tunas Jaya Desa Surabayan - Imam Syafi’i; Sofia Tri Septiawati (Pusat Riset dan Inovasi Nasional, 2024)
The Policy on Teachers' Main Duties as a Means of Developing Leadership Spirit for Teachers of Early Childhood Education Units (SPS) Tunas Jaya, Surabayan Village. Data collection was conducted through interviews with the Principal and Vice Principal as a step to assess the appropriateness of policy implementation by teachers at the Early Childhood Education Unit (SPS) Tunas Jaya, Surabayan Village, Sukodadi Subdistrict, Lamongan Regency.